2004
DOI: 10.1002/cncr.20276
|View full text |Cite
|
Sign up to set email alerts
|

Patterns and predictors of colorectal cancer test use in the adult U.S. population

Abstract: BACKGROUNDScreening is effective in reducing the incidence and mortality of colorectal cancer. Rates of colorectal cancer test use continue to be low.METHODSThe authors analyzed data from the National Health Interview Survey concerning the use of the home‐administered fecal occult blood test (FOBT) and sigmoidoscopy/colonoscopy/proctoscopy to estimate current rates of colorectal cancer test use and to identify factors associated with the use or nonuse of tests.RESULTSIn 2000, 17.1% of respondents reported unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

44
413
11
3

Year Published

2005
2005
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 478 publications
(471 citation statements)
references
References 24 publications
44
413
11
3
Order By: Relevance
“…Consistent with previously published literature regarding CRC screening, we have shown that test use varies by gender, age, income, smoking status [16,18-22]. Interestingly, respondents with higher income levels were more likely to have an endoscopy test.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Consistent with previously published literature regarding CRC screening, we have shown that test use varies by gender, age, income, smoking status [16,18-22]. Interestingly, respondents with higher income levels were more likely to have an endoscopy test.…”
Section: Discussionsupporting
confidence: 89%
“…Globally, only half the eligible population undergoes CRC screening [18-22]. In particular, screening for CRC is not commonly practiced in most Asian countries, and CRC screening behaviors in Asian populations remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Prior consultation with a gastroenterologist did not affect colonoscopy adherence rates in this study [7], in conflict with prior reports indicating that physician visitation in the preceding year and procedure recommendation by a physician positively influenced rates of adherence to CRC screening [6,10]. This discrepancy may reflect a higher-risk population with increased rates of comorbid conditions in their study subjects [7].…”
contrasting
confidence: 97%
“…The adherence rates in this study (overall 89.3 %) are considerably higher than in other published reports [3,6,10]. Reminder phone calls and postcards are effective in increasing rates of CRC screening [11].…”
contrasting
confidence: 66%
“…However, in the years under investigation, the overall impact of CRC screening is likely to have been limited, and gender differences in screening utilisation quite small compared to the major gender difference in CRC incidence and mortality. In particular, participation in Table 1 Age-adjusted mortality of colorectal cancer among men and women, and ages at which 10-year cumulative mortality among women reaches levels observed among men at ages 50, 55, and 60 endoscopic screening examinations was slightly lower rather than higher among women compared with men in the US (Seeff et al, 2004;Lieberman et al, 2005;Meissner et al, 2006), and could thus not explain the lower CRC mortality among women. Our analysis only considers the 'net differences' in CRC incidence and mortality between women and men, which might be owing to a variety of reasons.…”
Section: Discussionmentioning
confidence: 99%